Oil-resistant rubber sealing material for injection molding machine and method for preparing the same
Patent Information
- Application Number
- CN202611187389.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-06
- Publication Date
- 2026-10-13
AI Technical Summary
现阶段行业内用于注射机密封的橡胶基材主要分为氢化丁腈橡胶、氟橡胶两大体系,两类基材单独使用时均存在无法调和的性能短板,难以适配中大型精密注射机长期连续生产工况
1、本发明技术方案中的氢化丁腈橡胶与氟橡胶复配基体橡胶共混物:氢化丁腈橡胶分子链饱和程度高,赋予材料优良低温弹性与混炼加工流动性,降低密炼、模压成型难度;氟橡胶分子链含大量氟原子,氟原子屏蔽碳碳主链,大幅减弱液压油分子与橡胶分子链的溶胀渗透作用,单独使用可显著降低油液体积溶胀率。二者复配后,两类橡胶分子链相互穿插缠绕,形成互穿基础相结构,从基体根源改善单一橡胶性能短板。核壳型纳米管增强填料:以埃洛石纳米管中空管状结构为骨架,管内填充液体丁腈橡胶+纳米氧化锌复配增韧剂,中空管腔内部形成柔性核层,外力作用时柔性核层可吸收、分散应力,钝化裂纹扩展路径;氩气等离子体预交联使管内增韧剂形成轻度交联网络,避免高温加工时内部增韧剂迁移析出;复配氟硅烷偶联剂接枝于纳米管外壁构建疏水壳层,氟硅烷链段可与氟橡胶相容,硅烷烷氧基端与橡胶分子链形成化学键结合,大幅提升填料与基体界面粘结力。脉冲微波同步辅助接枝,微波能量均匀作用于悬浮液,提升硅烷分子活性,提高纳米管表面硅烷接枝覆盖率,消除填料团聚缺陷。复合硫化体系(过氧化二异丙苯+三烯丙基异氰脲酸酯):过氧化二异丙苯受热分解产生自由基,引发橡胶分子链交联;三烯丙基异氰脲酸酯含多不饱和双键,作为交联助剂参与交联反应,拓宽交联点位,形成连续、均匀致密的三维交联网络,提升交联密度,高温油环境下交联键不易断裂,降低压缩永久变形。聚四氟乙烯母粒:聚四氟乙烯分子链摩擦系数极低,混炼后均匀分散于橡胶基体摩擦表层,形成自润滑薄膜,减少密封件往复运动时摩擦损耗;同时氟元素可辅助阻隔油液渗透,进一步优化耐油性能。分级加工助剂(防老剂RD、硬脂酸、微晶石蜡):防老剂RD捕获橡胶热氧老化自由基,延缓高温工况下橡胶分子链降解;硬脂酸作为活化剂提升硫化体系反应效率,改善填料分散性;微晶石蜡迁移至材料表面形成防护薄膜,隔绝液压油与氧气侵蚀,三者按特定比例复配可协同稳定材料长期服役性能。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of rubber technology, specifically to an oil-resistant rubber sealing material for injection molding machines and its preparation method. Background Technology
[0002] The rubber seals used in the hydraulic system of injection molding machines are subjected to harsh conditions of continuous high-temperature hydraulic oil immersion, high-frequency reciprocating extrusion, and constant friction. The seals' resistance to oil swelling, high-temperature elasticity retention, wear resistance, and molding performance directly determine the operational stability and maintenance cycle of the injection molding equipment, making them indispensable and vulnerable components of the hydraulic system. Currently, the rubber substrates used for injection molding machine seals are mainly divided into two systems: hydrogenated nitrile rubber and fluororubber. Both types of substrates have inherent limitations when used alone, making them unsuitable for the long-term continuous production conditions of medium to large precision injection molding machines.
[0003] Hydrogenated nitrile butadiene rubber (NBR) has a high degree of molecular backbone saturation, excellent low-temperature elasticity, good flowability during mixing, and high tolerance for molding processes. However, its molecular chain lacks a fluorine shielding structure, making it prone to oil penetration and swelling after prolonged contact with high-temperature hydraulic oil. This leads to volume expansion, a significant decrease in hardness, and widening of the gap between sealing surfaces, causing leakage. Furthermore, under high-temperature reciprocating friction, the molecular chain is susceptible to thermo-oxidative aging, resulting in rapid wear and tear and sealing failure even after short-term use. Fluororubber, thanks to the shielding effect of fluorine atoms in its molecular chain, exhibits outstanding oil and high-temperature resistance. However, it suffers from high rigidity, significant elasticity loss at low temperatures, and large permanent deformation after high-frequency compression. Additionally, pure fluororubber has high viscosity, making compression molding difficult and resulting in a low yield rate for producing irregularly shaped seals. This makes it unsuitable for mass production of small-sized, complex-shaped seals using small precision injection molding machines.
[0004] To balance the performance shortcomings of the two types of rubber, the existing conventional improvement method is to prepare a binary matrix by simple physical blending of hydrogenated nitrile rubber and fluororubber. The two phases are simply mixed by mechanical mixing. The molecular chains of the two rubbers have poor compatibility, and the two phases are only held together by weak intermolecular forces. When the material is subjected to external extrusion and friction, microcracks are easily generated at the two phases interface, which directly reduces the tensile strength and tear resistance of the material.
[0005] Existing rubber sealing materials for injection molding machines suffer from problems such as poor formulation synergy, low filler reinforcement efficiency, insufficient overall oil and wear resistance of the matrix, and numerous molding process defects. The resulting seals are prone to swelling and leakage in high-temperature oil environments, exhibit poor compression resilience, and have short wear-resistant service life. This leads to frequent seal replacements and high downtime maintenance costs. Currently, the industry lacks an integrated solution that can balance moldability, long-term oil resistance stability, high-temperature elasticity retention, and long-lasting wear resistance, providing a space for technological improvement in the development of this invention. Summary of the Invention
[0006] To achieve the above objectives, the present invention provides the following technical solution: An oil-resistant rubber sealing material for injection molding machines comprises the following raw material components: a matrix rubber blend consisting of 60-80 parts of hydrogenated nitrile rubber and 20-40 parts of fluororubber; 12-28 parts of core-shell nanotube reinforcing filler; 3-6 parts of a composite vulcanization system; and 1-3 parts of processing aids.
[0007] As a further technical solution, the polymer toughening agent is a mixture of liquid nitrile rubber and nano zinc oxide with an average particle size of 30 nm at a mass ratio of 10:1.
[0008] As a further technical solution, the raw materials also include 8-12 parts of polytetrafluoroethylene masterbatch.
[0009] As a further technical solution, the composite vulcanization system is composed of dicumyl peroxide and triallyl isocyanurate in a mass ratio of 2:1.
[0010] As a further technical solution, the processing aids include antioxidant RD, stearic acid, and microcrystalline wax mixed in a mass ratio of 0.5~1.5:0.3~1:0.2~0.5.
[0011] As a further technical solution, the preparation steps of the core-shell nanotube reinforced filler are as follows: S21 tube internal vacuum filling: Halloysite nanotubes are placed in a vacuum oven, vacuumed to -0.095MPa and maintained for 30min, a polymer toughening agent preheated to 80℃ is injected and the vacuum is broken, soaked at normal pressure for 2h and then filtered, and the surface floating material is removed by rinsing with anhydrous ethanol to obtain tube internal filling nanotubes. S22 In-situ pre-crosslinking inside the tube: The tube-filled nanotube is laid flat on the sample stage of the plasma reaction chamber, and argon gas with a purity of 99.99% is introduced. It is treated for 5 to 10 minutes under the conditions of power 80~120W and pressure 20~30Pa to form a pre-crosslinked structure of polymer slurry inside the tube. S23 composite silane co-grafting: Pre-crosslinked nanotubes were dispersed in toluene to prepare a suspension with a nanotube mass fraction of 5%. A composite silane coupling agent was added, and a 0.5% glacial acetic acid aqueous solution was added dropwise to adjust the pH of the suspension to 4.5. The mixture was stirred at 70℃ for 5 h. After the reaction, the nanotubes were washed three times by centrifugation with anhydrous ethanol and dried at 80℃ for 12 h under a vacuum of -0.08~-0.1 MPa to obtain a core-shell nanotube reinforced filler.
[0012] As a further technical solution, the polymer toughening agent filled in the halloysite nanotubes in the core-shell nanotube reinforcing filler accounts for 30% to 40% of the mass of the halloysite nanotubes.
[0013] As a further technical solution, the compounded silane coupling agent is composed of γ-methacryloxypropyltrimethoxysilane and tridecafluorooctyltriethoxysilane in a mass ratio of 3:1, and its total amount is 10% to 15% of the original mass of the halloysite nanotubes.
[0014] As a further technical solution, the halloysite nanotubes have a diameter of 30~70nm and a length of 0.5~2μm.
[0015] As a further technical solution, in the process of co-grafting the compounded silane in step S23, pulsed microwave radiation is applied simultaneously to assist the reaction; the power of the microwave radiation is 800~1000W, and a pulse working mode is adopted, with 10s working and 20s intermittent in a single cycle, and the microwave radiation and stirring reaction are started and stopped synchronously.
[0016] A method for preparing an oil-resistant rubber sealing material for a shooting machine includes the following steps: S1 Stage Mixing: Hydrogenated nitrile rubber and fluororubber are put into a mixer and mixed at 100~120℃ for 5~8 minutes. Antioxidant and stearic acid are added, and the mixture is continued for 2 minutes before discharge. S2 two-stage mixing: Put the first-stage compound back into the internal mixer, add the core-shell nanotube reinforcing filler and polytetrafluoroethylene masterbatch, and mix at 90~110℃ for 6~10min. S3 Vulcanization Final Processing: Cool the two-stage compound rubber to below 60°C, add the composite vulcanization system and microcrystalline wax, mix for 3-5 minutes and then sheet out. S4 vulcanization molding: First, it is molded and vulcanized at 170℃ and 10MPa pressure for 10 minutes, and then placed in a 150℃ hot air oven for a second-stage vulcanization for 4 hours to obtain the sealing material.
[0017] Compared with the prior art, the beneficial effects of the present invention are: 1. The hydrogenated nitrile butadiene rubber and fluororubber blend in the technical solution of this invention: The hydrogenated nitrile butadiene rubber has a high degree of molecular chain saturation, which endows the material with excellent low-temperature elasticity and mixing fluidity, reducing the difficulty of internal mixing and molding; the fluororubber molecular chain contains a large number of fluorine atoms, which shield the carbon-carbon backbone, greatly reducing the swelling and penetration effect between hydraulic oil molecules and rubber molecular chains, and can significantly reduce the volume swelling rate of the oil when used alone. After the two are blended, the two types of rubber molecular chains interpenetrate and intertwine to form an interpenetrating basic phase structure, improving the shortcomings of single rubber performance from the root of the matrix. Core-shell nanotube reinforced filler: Using halloysite nanotubes with a hollow tubular structure as the framework, the tubes are filled with a mixture of liquid nitrile rubber and nano-zinc oxide as a toughening agent. A flexible core layer forms inside the hollow cavity, which absorbs and disperses stress under external force, thus blunting crack propagation paths. Argon plasma pre-crosslinking creates a slightly crosslinked network of the toughening agent inside the tube, preventing migration and precipitation of the toughening agent during high-temperature processing. A compounded fluorosilane coupling agent is grafted onto the outer wall of the nanotube to construct a hydrophobic shell. The fluorosilane segments are compatible with fluororubber, and the alkoxy ends of the silane form chemical bonds with the rubber molecular chains, significantly improving the interfacial adhesion between the filler and the matrix. Pulsed microwave synchronous assisted grafting ensures that microwave energy is uniformly applied to the suspension, enhancing the activity of silane molecules, increasing the silane grafting coverage on the nanotube surface, and eliminating filler agglomeration defects. Composite vulcanization system (dicumyl peroxide + triallyl isocyanurate): Dicumyl peroxide decomposes upon heating to generate free radicals, initiating cross-linking of rubber molecular chains; triallyl isocyanurate contains polyunsaturated double bonds, acting as a cross-linking aid in the cross-linking reaction, broadening the cross-linking sites, forming a continuous, uniform, and dense three-dimensional cross-linking network, increasing the cross-linking density, and making the cross-linking bonds less prone to breakage under high-temperature oil conditions, thus reducing compression set. Polytetrafluoroethylene masterbatch: Polytetrafluoroethylene molecular chains have an extremely low coefficient of friction. After mixing, it is uniformly dispersed on the friction surface of the rubber matrix, forming a self-lubricating film, reducing frictional loss during the reciprocating motion of the seals; simultaneously, fluorine helps to block oil penetration, further optimizing oil resistance. Graded processing aids (antioxidant RD, stearic acid, microcrystalline wax): Antioxidant RD captures free radicals in rubber under thermo-oxidative aging, delaying the degradation of rubber molecular chains under high-temperature conditions; stearic acid acts as an activator to improve the reaction efficiency of the vulcanization system and improve the dispersibility of fillers; microcrystalline wax migrates to the material surface to form a protective film, isolating hydraulic oil and oxygen from corrosion. The three are compounded in a specific ratio to synergistically stabilize the long-term service performance of the material.
[0018] 2. This invention employs a three-stage mixing and two-stage vulcanization process: the first stage involves high-temperature co-mixing to achieve full compatibility of the two rubbers and eliminate phase separation; the second stage involves medium-temperature mixing to gently disperse nanofillers and prevent damage to the pre-crosslinked structure inside the fillers caused by high temperatures; the third stage involves low-temperature final mixing to add to the vulcanization system and prevent premature scorching; the fourth stage involves compression molding for rapid molding and shaping; and the fifth stage involves low-temperature hot air vulcanization to eliminate internal residual stress, improve the crosslinking network, reduce internal micropores after molding, and block oil penetration channels.
[0019] 3. This solution is not a simple superposition of raw materials and modification processes, but rather a synergistic system formed through mutual cooperation: First, a binary rubber matrix is used to construct a basic framework that balances elasticity and oil resistance, while polytetrafluoroethylene masterbatch provides a lubrication barrier, solving the imbalance between oil resistance and wear resistance in single-phase rubber. Second, a core-shell nanotube filler modified in three steps serves as the core reinforcing unit. The internal flexible core layer addresses the shortcomings of inorganic fillers, such as high rigidity and susceptibility to cracking, while the external fluorosilane shell is compatible with both hydrogenated nitrile butadiene rubber and fluororubber two-phase matrices, achieving chemical bonding between the filler and the two-phase rubber, avoiding stress concentration caused by filler agglomeration, and simultaneously improving tensile strength and tear resistance. Third, the composite vulcanization system relies on... Uniformly distributed core-shell fillers generate additional crosslinking sites at the filler-rubber interface. The crosslinking network penetrates both the rubber matrix and the filler surface, allowing external loads to be uniformly transferred to the nanotubes through the continuous crosslinking network, significantly reducing high-temperature compression set. Graded compounding processing aids assist in stabilizing the crosslinking network from the perspectives of anti-aging, filler dispersion, and surface protection, inhibiting molecular chain degradation and oil swelling under high-temperature oil conditions. Finally, graded temperature-controlled mixing and a two-stage vulcanization process match the characteristics of the above raw material system: high-temperature co-mixing ensures rubber compatibility, medium-temperature mixing protects the nanotube core-shell structure from failure, low-temperature vulcanization avoids scorching, and two-stage vulcanization eliminates molding porosity, amplifying the synergistic advantages of the formulation from a processing perspective. Under this overall synergistic mechanism, filler reinforcement, rubber matrix, vulcanization network, lubrication and protection, and molding process are mutually compatible, with no performance offsetting each other, and the advantages of each component are mutually amplified.
[0020] 4. The oil-resistant rubber sealing material for injection molding machines prepared by this invention solves the problems of poor oil resistance and swelling, rapid high-temperature elastic decay, short wear life, and difficult molding and processing of existing sealing materials. Compared with traditional rubber, this material has a volume change rate of less than 2% after long-term immersion in hydraulic oil at 150℃, and a significantly reduced hardness decay; tensile strength is increased by more than 20%, and the permanent deformation rate of reciprocating compression is controlled within 13%; Akron wear volume is greatly reduced, and wear service life is more than doubled. At the same time, the three-stage graded mixing process produces excellent flowability, eliminates filler agglomeration and rubber delamination problems, and results in a high yield rate for compression molding. It is suitable for the mass industrial production of various irregularly shaped injection molding machine seals, effectively reducing the frequency of seal replacement in the hydraulic system of injection molding machines, reducing equipment downtime maintenance costs, and possessing outstanding industrial application value and economic advantages. Detailed Implementation
[0021] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0022] This invention provides an oil-resistant rubber sealing material for injection molding machines, comprising the following raw material components: a matrix rubber blend consisting of 60-80 parts of hydrogenated nitrile rubber and 20-40 parts of fluororubber; 12-28 parts of core-shell nanotube reinforcing filler; 3-6 parts of a composite vulcanization system; and 1-3 parts of processing aids.
[0023] In this invention, the matrix rubber blend is composed of hydrogenated nitrile butadiene rubber and fluororubber. The preferred amount of hydrogenated nitrile butadiene rubber is 60-80 parts, and the preferred amount of fluororubber is 20-40 parts; more preferably, the amount of hydrogenated nitrile butadiene rubber is 70 parts, and the amount of fluororubber is 30 parts. The blending of these two materials synergistically improves the material's oil resistance, high-temperature resistance, and mechanical strength, making it suitable for the stringent sealing requirements of injection molding machines.
[0024] In this invention, the amount of the core-shell nanotube reinforcing filler is preferably 12-28 parts, more preferably 20 parts. The core-shell nanotube reinforcing filler uses halloysite nanotubes as a framework, obtained through in-tube filling, in-situ pre-crosslinking, and surface grafting modification, and has both reinforcing and toughening effects. The halloysite nanotubes preferably have a diameter of 30-70 nm and a length of 0.5-2 μm; more preferably, a diameter of 50 nm and a length of 1.25 μm.
[0025] In this invention, the polymer toughening agent used for the tube filling is a mixture of liquid nitrile rubber and nano-zinc oxide with an average particle size of 30 nm at a mass ratio of 10:1. The mass ratio of the polymer toughening agent filling the halloysite nanotubes in the core-shell nanotube reinforced filler to the mass of the halloysite nanotubes is preferably 30% to 40%, more preferably 35%.
[0026] In this invention, the preparation steps of the core-shell nanotube reinforced filler are as follows: S21 Vacuum filling inside the tube: Halloysite nanotubes are placed in a vacuum oven, evacuated to -0.095 MPa and maintained for 30 min, a polymer toughening agent preheated to 80°C is injected, the vacuum is broken, and the nanotubes are soaked at normal pressure for 2 h, then filtered. Surface floating material is removed by rinsing with anhydrous ethanol to obtain the in-situ filled nanotubes. S22 In-situ pre-crosslinking inside the tube: The in-situ filled nanotubes are laid flat on the sample stage of the plasma reaction chamber, and 99.99% pure argon gas is introduced. The nanotubes are treated for 5-10 min at a power of 80-120 W and a pressure of 20-30 Pa to form a pre-crosslinked structure in the polymer slurry inside the tube. The plasma treatment power is preferably 80-120 W, more preferably 100 W; the pressure is preferably 20-30 Pa, more preferably 25 Pa; and the treatment time is preferably 5-10 min, more preferably 7.5 min. S23 Silane Co-grafting: Pre-crosslinked nanotubes are dispersed in toluene to prepare a suspension with a nanotube mass fraction of 5%. A silane coupling agent is added, and a 0.5% glacial acetic acid aqueous solution is added dropwise to adjust the pH of the suspension to 4.5. The mixture is stirred at 70°C for 5 hours. After the reaction, the nanotubes are washed three times by centrifugation with anhydrous ethanol and dried at 80°C for 12 hours under a vacuum of -0.08 to -0.1 MPa to obtain a core-shell nanotube reinforced filler. The silane coupling agent is a mixture of γ-methacryloyloxypropyltrimethoxysilane and tridecafluorooctyltriethoxysilane in a mass ratio of 3:1. The total amount of the silane coupling agent is preferably 10% to 15% of the original mass of the halloysite nanotubes, and more preferably 12.5%. In step S23, during the co-grafting of compound silanes, pulsed microwave radiation is applied simultaneously to assist the reaction; the power of the microwave radiation is preferably 800~1000W, more preferably 900W; a pulse working mode is adopted, with 10s operation and 20s interval in a single cycle, and the microwave radiation and stirring reaction are started and stopped synchronously.
[0027] In this invention, the amount of the composite vulcanization system is preferably 3 to 6 parts, more preferably 4.5 parts. The composite vulcanization system is composed of dicumyl peroxide and triallyl isocyanurate in a mass ratio of 2:1, which can achieve efficient crosslinking of the blended rubber and form a uniform crosslinking network.
[0028] In this invention, the preferred amount of the processing aid is 1 to 3 parts, more preferably 2 parts. The processing aid includes antioxidant RD, stearic acid, and microcrystalline wax, and the preferred mass ratio of the three is 0.5 to 1.5: 0.3 to 1: 0.2 to 0.5, more preferably 1: 0.65: 0.35.
[0029] In this invention, the raw materials also include polytetrafluoroethylene masterbatch, preferably in an amount of 8 to 12 parts, more preferably 10 parts, which can further improve the wear resistance and self-lubricating properties of the material.
[0030] This invention also provides a method for preparing the oil-resistant rubber sealing material for injection molding machines, comprising the following steps: S1 First-stage mixing: Hydrogenated nitrile rubber and fluororubber are fed into an internal mixer and mixed at 100-120°C for 5-8 minutes. Antioxidant and stearic acid are added, and mixing continues for 2 minutes before discharge. The preferred temperature for the first-stage mixing is 100-120°C, more preferably 110°C; the preferred mixing time is 5-8 minutes, more preferably 6.5 minutes. S2 Second-stage mixing: The first-stage mixed rubber is re-fed into the internal mixer, and core-shell nanotube reinforcing filler and polytetrafluoroethylene masterbatch are added. Mixing is carried out at 90-110°C for 6-10 minutes. The preferred temperature for the second-stage mixing is 90-110°C, more preferably 100°C; the preferred mixing time is 6-10 minutes, more preferably 8 minutes. S3 Final vulcanization: The second-stage mixed rubber is cooled to below 60°C, and a composite vulcanization system and microcrystalline wax are added. Mixing is carried out for 3-5 minutes before sheeting. The mixing time for the final sulfur addition is preferably 3-5 minutes, more preferably 4 minutes. S4 vulcanization molding: First, it is molded and vulcanized at 170℃ and 10MPa pressure for 10 minutes, and then placed in a 150℃ hot air oven for a second-stage vulcanization for 4 hours to obtain the sealing material.
[0031] The oil-resistant rubber sealing material for injection molding machines provided by this invention uses a blend matrix of hydrogenated nitrile rubber and fluororubber, combined with core-shell nanotube reinforcing fillers and a composite vulcanization system. While ensuring excellent mechanical properties, it significantly improves the material's oil resistance, high-temperature compression set resistance, and wear resistance, meeting the long-term use requirements of injection molding machine seals in high-temperature hydraulic oil environments and extending the service life of the seals. At the same time, the manufacturing process is controllable, with good molding stability, making it suitable for industrial mass production.
[0032] This invention provides an oil-resistant rubber sealing material for injection molding machines and its preparation method. The raw materials include a matrix rubber blend composed of 60-80 parts hydrogenated nitrile rubber and 20-40 parts fluororubber, 12-28 parts core-shell nanotube reinforcing filler, 3-6 parts composite vulcanization system, 1-3 parts processing aids, and 8-12 parts polytetrafluoroethylene masterbatch. The core-shell nanotubes are modified in three steps: vacuum filling inside the tubes, in-situ pre-crosslinking, and co-grafting with compound silanes. The sealing material is then prepared using a three-stage mixing and two-stage vulcanization process. Compared with existing technologies, this invention uses a core-shell reinforcing filler with a specific structure and a blended matrix, combined with corresponding processes to achieve synergistic effects of multiple components. This solves the problems of insufficient oil resistance, high-temperature resistance, and wear resistance in ordinary rubber sealing materials, while avoiding the defects of weak interfacial bonding between the filler and the matrix and significant stress concentration. This comprehensively improves the service life and adaptability of the seals.
[0033] To further illustrate the present invention, the following examples provide a detailed description. The hydrogenated nitrile rubber, fluororubber, halloysite nanotubes, liquid nitrile rubber, nano zinc oxide, dicumyl peroxide, triallyl isocyanurate, antioxidant RD, stearic acid, microcrystalline wax, polytetrafluoroethylene masterbatch, and silane coupling agent used in the following examples are all commercially available industrial-grade conventional products.
[0034] Example 1: (1) Preparation of core-shell nanotube reinforced fillers: S21 Vacuum Filling: Halloysite nanotubes with a diameter of 30 nm and a length of 0.5 μm were placed in a vacuum oven, evacuated to -0.095 MPa and maintained for 30 min, and then a polymer toughening agent preheated to 80 °C was injected. After the vacuum was broken, the nanotubes were soaked at normal pressure for 2 h and then filtered. The surface floating material was removed by rinsing with anhydrous ethanol to obtain the internally filled nanotubes. The polymer toughening agent was a mixture of liquid nitrile rubber and nano zinc oxide with an average particle size of 30 nm at a mass ratio of 10:1. The mass of the polymer toughening agent used for filling accounted for 30% of the mass of the halloysite nanotubes.
[0035] S22 In-situ pre-crosslinking inside the tube: The tube-filled nanotube is laid flat on the sample stage of the plasma reaction chamber, and argon gas with a purity of 99.99% is introduced. It is treated for 5 minutes under the conditions of 80W power and 20Pa pressure to form a pre-crosslinked structure of polymer slurry inside the tube.
[0036] S23 Silane Co-grafting: Pre-crosslinked nanotubes were dispersed in toluene to prepare a suspension with a nanotube mass fraction of 5%. A silane coupling agent was added, and a 0.5% glacial acetic acid aqueous solution was added dropwise to adjust the pH of the suspension to 4.5. The mixture was stirred at 70℃ for 5 hours. During the reaction, pulsed microwave radiation was applied simultaneously to assist the reaction. The microwave radiation power was 800W, and a pulse working mode was adopted, with a single cycle of 10 seconds and a 20-second interval. The microwave radiation and stirring reaction were started and stopped synchronously. After the reaction, the nanotubes were washed three times by centrifugation with anhydrous ethanol and dried at 80℃ for 12 hours under a vacuum of -0.08MPa to obtain a core-shell nanotube reinforced filler. The silane coupling agent was composed of γ-methacryloyloxypropyltrimethoxysilane and tridecafluorooctyltriethoxysilane in a mass ratio of 3:1, and its total amount was 10% of the original mass of halloysite nanotubes.
[0037] (2) Preparation of oil-resistant rubber sealing material for injection molding machines: S1 First stage mixing: 60 parts of hydrogenated nitrile rubber and 40 parts of fluororubber are put into an internal mixer and mixed at 100°C for 5 minutes. Antioxidant RD and stearic acid are added, and the mixture is continued to be mixed for 2 minutes before discharge. The mass ratio of antioxidant RD to stearic acid is 0.5:0.3.
[0038] S2 two-stage mixing: Put the first-stage compound back into the internal mixer, add 12 parts of core-shell nanotube reinforcing filler and 8 parts of polytetrafluoroethylene masterbatch, and mix at 90°C for 6 minutes.
[0039] S3 Vulcanization Final Processing: Cool the two-stage compound rubber to below 60℃, add 3 parts of the composite vulcanization system and microcrystalline wax, mix for 3 minutes and then sheet; the composite vulcanization system is composed of dicumyl peroxide and triallyl isocyanurate in a mass ratio of 2:1, the mass ratio of microcrystalline wax to antioxidant RD and stearic acid is 0.2:0.5:0.3, and the total amount of processing aids is 1 part.
[0040] S4 vulcanization molding: First, it is molded and vulcanized at 170℃ and 10MPa pressure for 10 minutes, and then placed in a 150℃ hot air oven for a second-stage vulcanization for 4 hours to obtain the sealing material.
[0041] Example 2: (1) Preparation of core-shell nanotube reinforced fillers: S21 Vacuum Filling: Halloysite nanotubes with a diameter of 70 nm and a length of 2 μm were placed in a vacuum oven, evacuated to -0.095 MPa and maintained for 30 min, and then a polymer toughening agent preheated to 80 °C was injected. After the vacuum was broken, the nanotubes were soaked at normal pressure for 2 h and then filtered. The surface floating material was removed by rinsing with anhydrous ethanol to obtain the internally filled nanotubes. The polymer toughening agent was a mixture of liquid nitrile rubber and nano zinc oxide with an average particle size of 30 nm at a mass ratio of 10:1. The mass of the polymer toughening agent used for filling accounted for 40% of the mass of the halloysite nanotubes.
[0042] S22 In-situ pre-crosslinking inside the tube: The nanotube filled with the tube is laid flat on the sample stage of the plasma reaction chamber, and argon gas with a purity of 99.99% is introduced. The tube is treated for 10 minutes under the conditions of 120W power and 30Pa pressure to form a pre-crosslinked structure of polymer slurry inside the tube.
[0043] S23 Silane Co-grafting: Pre-crosslinked nanotubes were dispersed in toluene to prepare a suspension with a nanotube mass fraction of 5%. A silane coupling agent was added, and a 0.5% glacial acetic acid aqueous solution was added dropwise to adjust the pH of the suspension to 4.5. The mixture was stirred at 70℃ for 5 hours. During the reaction, pulsed microwave radiation was applied simultaneously to assist the reaction. The microwave radiation power was 1000W, and a pulse working mode was adopted, with a single cycle of 10s and a 20s interval. The microwave radiation and stirring reaction were started and stopped synchronously. After the reaction, the nanotubes were washed three times by centrifugation with anhydrous ethanol and dried at 80℃ for 12 hours under a vacuum of -0.1MPa to obtain a core-shell nanotube reinforced filler. The silane coupling agent was composed of γ-methacryloyloxypropyltrimethoxysilane and tridecafluorooctyltriethoxysilane in a mass ratio of 3:1, and its total amount was 15% of the original mass of halloysite nanotubes.
[0044] (2) Preparation of oil-resistant rubber sealing material for injection molding machines: S1 First stage mixing: 80 parts of hydrogenated nitrile rubber and 20 parts of fluororubber are put into an internal mixer and mixed at 120°C for 8 minutes. Antioxidant RD and stearic acid are added, and the mixture is continued to be mixed for 2 minutes before discharge. The mass ratio of antioxidant RD to stearic acid is 1.5:1.
[0045] S2 two-stage mixing: Put the first-stage compound back into the internal mixer, add 28 parts of core-shell nanotube reinforcing filler and 12 parts of polytetrafluoroethylene masterbatch, and mix at 110°C for 10 minutes.
[0046] S3 final vulcanization: Cool the two-stage compound rubber to below 60℃, add 6 parts of the composite vulcanization system and microcrystalline wax, mix for 5 minutes and then sheet; the composite vulcanization system is composed of dicumyl peroxide and triallyl isocyanurate in a mass ratio of 2:1, the mass ratio of microcrystalline wax to antioxidant RD and stearic acid is 0.5:1.5:1, and the total amount of processing aids is 3 parts.
[0047] S4 vulcanization molding: First, it is molded and vulcanized at 170℃ and 10MPa pressure for 10 minutes, and then placed in a 150℃ hot air oven for a second-stage vulcanization for 4 hours to obtain the sealing material.
[0048] Example 3: (1) Preparation of core-shell nanotube reinforced fillers: S21 Vacuum Filling: Halloysite nanotubes with a diameter of 50 nm and a length of 1.25 μm were placed in a vacuum oven, evacuated to -0.095 MPa and maintained for 30 min, and then a polymer toughening agent preheated to 80 °C was injected. After the vacuum was broken, the nanotubes were soaked at normal pressure for 2 h and then filtered. The surface floating material was removed by rinsing with anhydrous ethanol to obtain the internally filled nanotubes. The polymer toughening agent was a mixture of liquid nitrile rubber and nano zinc oxide with an average particle size of 30 nm at a mass ratio of 10:1. The mass of the polymer toughening agent used for filling accounted for 35% of the mass of the halloysite nanotubes.
[0049] S22 In-situ pre-crosslinking inside the tube: The nanotube filled with the tube is laid flat on the sample stage of the plasma reaction chamber, and argon gas with a purity of 99.99% is introduced. It is treated for 7.5 minutes under the conditions of 100W power and 25Pa pressure to form a pre-crosslinked structure of polymer slurry inside the tube.
[0050] S23 Silane Co-grafting: Pre-crosslinked nanotubes were dispersed in toluene to prepare a suspension with a nanotube mass fraction of 5%. A silane coupling agent was added, and a 0.5% glacial acetic acid aqueous solution was added dropwise to adjust the pH of the suspension to 4.5. The mixture was stirred at 70℃ for 5 hours. During the reaction, pulsed microwave radiation was applied simultaneously to assist the reaction. The microwave radiation power was 900W, and a pulse working mode was adopted, with a single cycle of 10 seconds and a 20-second interval. The microwave radiation and stirring reaction were started and stopped synchronously. After the reaction, the nanotubes were washed three times by centrifugation with anhydrous ethanol and dried at 80℃ for 12 hours under a vacuum of -0.09MPa to obtain a core-shell nanotube reinforced filler. The silane coupling agent was composed of γ-methacryloyloxypropyltrimethoxysilane and tridecafluorooctyltriethoxysilane in a mass ratio of 3:1, and its total amount was 12.5% of the original mass of halloysite nanotubes.
[0051] (2) Preparation of oil-resistant rubber sealing material for injection molding machines: S1 First stage mixing: 70 parts of hydrogenated nitrile rubber and 30 parts of fluororubber are put into an internal mixer and mixed at 110°C for 6.5 minutes. Antioxidant RD and stearic acid are added, and the mixture is continued to be mixed for 2 minutes before discharge. The mass ratio of antioxidant RD to stearic acid is 1:0.65.
[0052] S2 two-stage mixing: Put the first-stage compound back into the internal mixer, add 20 parts of core-shell nanotube reinforcing filler and 10 parts of polytetrafluoroethylene masterbatch, and mix at 100°C for 8 minutes.
[0053] S3 Vulcanization Final Processing: Cool the two-stage compound rubber to below 60℃, add 4.5 parts of the composite vulcanization system and microcrystalline wax, mix for 4 minutes and then sheet; the composite vulcanization system is composed of dicumyl peroxide and triallyl isocyanurate in a mass ratio of 2:1, the mass ratio of microcrystalline wax to antioxidant RD and stearic acid is 0.35:1:0.65, and the total amount of processing aids is 2 parts.
[0054] S4 vulcanization molding: First, it is molded and vulcanized at 170℃ and 10MPa pressure for 10 minutes, and then placed in a 150℃ hot air oven for a second-stage vulcanization for 4 hours to obtain the sealing material.
[0055] Comparative Example 1: The preparation method of Example 3 is adopted, except that: in step (2), core-shell nanotube reinforcing filler is not used, but replaced with the same amount of unmodified original halloysite nanotubes. The other raw materials, amounts and process parameters are the same as those in Example 3.
[0056] Comparative Example 2: The preparation method of Example 3 is adopted, except that: in step (1), the tube is not filled with a vacuum polymer toughening agent, and the original halloysite nanotubes are directly subjected to subsequent plasma treatment and silane grafting. The remaining process parameters are the same as those of Example 3.
[0057] Comparative Example 3: The preparation method of Example 3 is adopted, except that: in the S23 compound silane co-grafting process of step (1), pulsed microwave radiation is not applied to assist the reaction, and only conventional stirring reaction is used. The remaining process parameters are the same as those of Example 3.
[0058] Comparative Example 4: The preparation method of Example 3 is adopted, except that: the matrix rubber in step (2) does not contain fluororubber, and all of them are 100 parts of hydrogenated nitrile rubber. The other raw materials, dosages and process parameters are the same as those in Example 3.
[0059] test: Experiment 1: Oil resistance test Test Method: Each sample was prepared as a circular specimen with a diameter of 29 mm and a thickness of 6 mm. Following the general test method for the liquid resistance of rubber, the specimen was completely immersed in standard test oil No. 1 and placed in a constant temperature oven at 150℃ for 72 hours. After removal, the surface oil was quickly blotted dry with filter paper, and the volume and Shore A hardness of the specimen before and after immersion were immediately measured. The volume change rate and hardness change value were calculated. Each specimen was tested in triplicate, and the average value was taken. The test results are shown in Table 1.
[0060] Table 1. Oil resistance test results
[0061] As shown in Table 1, the volume change rate of Examples 1-3 was less than 2%, and the hardness change was less than 3.5 degrees, indicating excellent oil resistance. Comparative Example 1 used unmodified halloysite nanotubes, resulting in weak interfacial bonding between the filler and the rubber matrix, easily forming oil penetration channels, leading to a significant increase in volume change rate and hardness change. Comparative Example 2 did not use in-tube toughening agent filling, resulting in decreased filler-matrix interfacial compatibility, poorer crosslinking network uniformity, and a slight decrease in oil resistance. Comparative Example 3 did not use microwave-assisted grafting, resulting in a low silane grafting rate and insufficient filler surface modification effect, leading to slightly lower oil resistance than the Examples. Comparative Example 4 did not add fluororubber, and the matrix rubber itself had insufficient oil resistance, therefore exhibiting the largest volume change rate and hardness change, and the worst oil resistance.
[0062] Experiment 2: Mechanical and compressive permanent deformation properties test: Test methods: Tensile properties were tested using dumbbell-shaped Type I specimens, following the general test method for rubber tensile properties. The test was conducted at room temperature with a tensile rate of 500 mm / min. Tensile strength and elongation at break were recorded. Each specimen was tested in parallel five times, and the average value was taken. Compression set was tested using cylindrical specimens with a compression ratio of 25%. The specimens were placed at 150℃ for 22 hours, then removed and placed at room temperature for 30 minutes. The height of the recovered specimens was measured, and the compression set rate was calculated. Each specimen was tested in parallel three times, and the average value was taken. The test results are shown in Table 2.
[0063] Table 2 Test Results of Mechanical and Compressive Permanent Deformation Properties
[0064] As shown in Table 2, the tensile strength and elongation at break of the examples are both at a high level, with low compression set and excellent elastic recovery. The toughening agent inside the core-shell nanotube reinforced filler and the surface grafting structure can effectively transfer stress, while simultaneously passively blocking crack propagation and improving both strength and toughness; the uniform crosslinking network also ensures low compression set. In Comparative Example 1, the unmodified filler has poor interfacial bonding with the matrix, resulting in significant stress concentration, a substantial decrease in tensile strength, and a significant increase in compression set. Comparative Example 2 lacks the toughening component inside the tube, resulting in insufficient toughening effect and a decrease in elongation at break and compression set performance. In Comparative Example 3, the silane grafting is insufficient, the interfacial bonding is weak, and both mechanical and compressive properties decrease. In Comparative Example 4, the crosslinking network of the single hydrogenated nitrile rubber matrix has slightly poor uniformity, and its elasticity retention at high temperatures is weaker than that of the blend system, resulting in a higher compression set.
[0065] Experiment 3: Abrasion resistance test: Test method: An Akron abrasion testing machine was used for testing. The sample size was 32mm × 12mm × 6mm, the sample inclination angle was 15°, the applied normal load was 26.7N, the grinding wheel speed was 33r / min, and the total friction stroke was 1.61km. Before testing, the sample was placed at standard room temperature for 24 hours, and the initial mass was weighed. After testing, the sample mass was weighed again, and the wear volume was calculated based on the sample density. Each sample was tested twice in parallel, and the average value was taken. The test results are shown in Table 3.
[0066] Table 3. Test results of wear resistance performance
[0067] As shown in Table 3, the wear volume of the examples is significantly lower than that of the comparative examples, indicating excellent wear resistance. Core-shell nanotubes can effectively bear frictional stress, and combined with the self-lubricating effect of the PTFE masterbatch, reduce the coefficient of friction and decrease material wear. In Comparative Example 1, the unmodified filler easily detaches from the matrix, forming abrasive particles that exacerbate wear, resulting in a significant increase in wear volume. In Comparative Example 2, the filler-matrix interface bonding is weak, and the filler is easily pulled out during friction, leading to a decrease in wear resistance. In Comparative Example 3, the grafting effect is insufficient, the reinforcing effect of the filler is not fully utilized, and the wear amount increases. In Comparative Example 4, the lack of fluororubber contribution to friction resistance, and the weaker wear resistance of the matrix compared to the blend system, result in a higher wear volume.
[0068] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to the specific implementations described. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. An oil-resistant rubber sealing material for injection molding machines, characterized in that, It includes the following raw material components: a matrix rubber blend consisting of 60-80 parts hydrogenated nitrile rubber and 20-40 parts fluororubber; 12-28 parts core-shell nanotube reinforcing filler; 3-6 parts composite vulcanization system; and 1-3 parts processing aids.
2. The oil-resistant rubber sealing material for injection molding machines according to claim 1, characterized in that, The polymer toughening agent is a mixture of liquid nitrile rubber and nano zinc oxide with an average particle size of 30 nm at a mass ratio of 10:
1.
3. The oil-resistant rubber sealing material for injection molding machines according to claim 1, characterized in that, The raw materials also include 8-12 parts of polytetrafluoroethylene masterbatch.
4. The oil-resistant rubber sealing material for injection molding machines according to claim 1, characterized in that, The composite vulcanization system is composed of dicumyl peroxide and triallyl isocyanurate in a mass ratio of 2:
1.
5. The oil-resistant rubber sealing material for injection molding machines according to claim 1, characterized in that, The processing aids include antioxidant RD, stearic acid, and microcrystalline wax mixed in a mass ratio of 0.5~1.5:0.3~1:0.2~0.
5.
6. The oil-resistant rubber sealing material for injection molding machines according to claim 1, characterized in that, The preparation steps of the core-shell nanotube reinforced filler are as follows: S21 tube internal vacuum filling: Halloysite nanotubes are placed in a vacuum oven, vacuumed to -0.095MPa and maintained for 30min, a polymer toughening agent preheated to 80℃ is injected and the vacuum is broken, soaked at normal pressure for 2h and then filtered, and the surface floating material is removed by rinsing with anhydrous ethanol to obtain tube internal filling nanotubes. S22 In-situ pre-crosslinking inside the tube: The tube-filled nanotube is laid flat on the sample stage of the plasma reaction chamber, and argon gas with a purity of 99.99% is introduced. It is treated for 5 to 10 minutes under the conditions of power 80~120W and pressure 20~30Pa to form a pre-crosslinked structure of polymer slurry inside the tube. S23 composite silane co-grafting: Pre-crosslinked nanotubes were dispersed in toluene to prepare a suspension with a nanotube mass fraction of 5%. A composite silane coupling agent was added, and a 0.5% glacial acetic acid aqueous solution was added dropwise to adjust the pH of the suspension to 4.
5. The mixture was stirred at 70℃ for 5 h. After the reaction, the nanotubes were washed three times by centrifugation with anhydrous ethanol and dried at 80℃ for 12 h under a vacuum of -0.08~-0.1 MPa to obtain a core-shell nanotube reinforced filler.
7. The oil-resistant rubber sealing material for injection molding machines according to claim 6, characterized in that, In core-shell nanotube reinforced fillers, the polymer toughening agent filling the halloysite nanotubes accounts for 30% to 40% of the mass of the halloysite nanotubes.
8. The oil-resistant rubber sealing material for injection molding machines according to claim 6, characterized in that, The compounded silane coupling agent is composed of γ-methacryloxypropyltrimethoxysilane and tridecafluorooctyltriethoxysilane in a mass ratio of 3:1, and its total amount is 10% to 15% of the original mass of the halloysite nanotubes; the diameter of the halloysite nanotubes is 30 to 70 nm and the length is 0.5 to 2 μm.
9. The oil-resistant rubber sealing material for injection molding machines according to claim 6, characterized in that, In step S23, during the co-grafting of compound silanes, pulsed microwave radiation is applied simultaneously to assist the reaction; the power of the microwave radiation is 800~1000W, and a pulse working mode is adopted, with a single cycle of 10s and an interval of 20s, and the microwave radiation and stirring reaction are started and stopped synchronously.
10. A method for preparing an oil-resistant rubber sealing material for an injection molding machine as described in any one of claims 1 to 9, characterized in that, Includes the following steps: S1 Stage Mixing: Hydrogenated nitrile rubber and fluororubber are put into a mixer and mixed at 100~120℃ for 5~8 minutes. Antioxidant and stearic acid are added, and the mixture is continued for 2 minutes before discharge. S2 two-stage mixing: Put the first-stage compound back into the internal mixer, add the core-shell nanotube reinforcing filler and polytetrafluoroethylene masterbatch, and mix at 90~110℃ for 6~10min. S3 Vulcanization Final Processing: Cool the two-stage compound rubber to below 60°C, add the composite vulcanization system and microcrystalline wax, mix for 3-5 minutes and then sheet out. S4 vulcanization molding: First, it is molded and vulcanized at 170℃ and 10MPa pressure for 10 minutes, and then placed in a 150℃ hot air oven for a second-stage vulcanization for 4 hours to obtain the sealing material.